2009
DOI: 10.1177/0891241609342230
|View full text |Cite
|
Sign up to set email alerts
|

Police Academy Socialization: Understanding the Lessons Learned in a Paramilitary-Bureaucratic Organization

Abstract: Even as community policing has emerged as the dominant paradigm, research indicates that police agencies continue to be highly militaristic and bureaucratic in structure and culture. This article reports findings from an observational study of recruit training at a police academy that had introduced a new curriculum emphasizing community policing and problem solving. The article explores the socialization that takes place there to see how the tension between traditional and community policing is resolved. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(142 citation statements)
references
References 34 publications
5
134
1
2
Order By: Relevance
“…It has been reported that while in the training academy recruits see all instructors, regardless of sworn rank or civilian position, as holding a position of authority and status (Chappell & Lanza-Kaduce, 2010). Police agencies should insure that all academy personnel, whenever possible, demonstrate an attitude that is unaccepting of unnecessary force, even milder forms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that while in the training academy recruits see all instructors, regardless of sworn rank or civilian position, as holding a position of authority and status (Chappell & Lanza-Kaduce, 2010). Police agencies should insure that all academy personnel, whenever possible, demonstrate an attitude that is unaccepting of unnecessary force, even milder forms.…”
Section: Resultsmentioning
confidence: 99%
“…Officers are expected to frame their use of coercion based on their experience in its use and their exposure to human suffering (Muir, 1977). The studies of police recruits tend to focus on an overall 'socialization' process while in the academy (Chappell & Lanza-Kaduce, 2010;Ford, 2003). It is, therefore, reasonable to study policing at a point that Barker (1999), McElroy et al (1999), and Muir (1977) were unable to: examine the attitudes of police recruits toward the use of unnecessary force prior to any exposure to police work.…”
Section: Current Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…Officers are trained to a disciplinary standard that clearly demarks power to the officer and subservience to the citizen who has broken "the rules." Intensive socialization process occurs during training to prepare the officer "for the realities of potentially dangerous jobs that incorporate the use of force" (Chappell & Lanza-Kaduce, 2010). Training instills an esprit de corps to form a tightly bound officer community.…”
Section: Discussionmentioning
confidence: 99%
“…Law enforcement officers have their own bias and through their paramilitary training which includes an intensive socialization process "for the realities of potentially dangerous jobs that incorporate the use of force" (Chappell & Lanza-Kaduce, 2010). Law enforcement training instills an esprit de corps, forms the officers into a tightly bound cohort, increases cohesion, strengthens relationships within the officer community, and creates a dialog of us vs. them that excludes the citizen community that they are engaged to protect (Chappell & Lanza-Kaduce, 2010). Public dialog about law enforcement varies; multiculturalism has changed the community which no longer speaks with one voice.…”
Section: Public Interest Statementmentioning
confidence: 99%